Human erythrocyte antigens in Brazilian Capuchin monkeys (Sapajus sp.) - Resende, Lucilene Silva Ruiz e [UNESP]; da Silva, Adaize Pereira [UNESP]; Garcia, Patrícia Carvalho [UNESP]; de Oliveira, Francisco Szneczuk [UNESP]; Bueno, Lais Melício Cintra [UNESP]; Secco, Valéria Nogueira Dias Paes [UNESP]; Zanini, José Mauro [UNESP]; Rahal, Sheila Canevese [UNESP]; Teixeira, Carlos Roberto [UNESP] (Wiley, 2018)
Background: Investigation of erythrocyte antigens in New World monkeys, especially in the Brazilian ones, is scant and incomplete. Methods: Determining the presence of 29 erythrocyte antigens from 11 human blood group systems (ABO, H, Rh, Kell, Duffy, Kidd, Lewis, P, MNS, Lutheran and Diego) on erythrocytes in nine Capuchin monkeys (Sapajus sp.). Results: A majority (20 of 29) of human erythrocyte antigens were not found in this monkey genus. Erythrocyte phenotyping was very similar within this animal group, as five Capuchin monkeys differed from the other four in the ABO system only. Conclusion: The erythrocyte phenotype for this group of animals is less diversified than in humans. Some monkey erythrocyte antigens were similar in frequency, whereas others were different from those observed in human ethnicities.
Keywords: blood; phenotyping; primates